Maximizing binary interactome mapping with a minimal number of assays - Soon Gang Choi (Nature Portfolio, 2019)
Comprehensive mapping of binary protein-protein interactions requires to combine several complementary assays. Here, the authors show that complete coverage could be reached with a minimal number of assays as long as they explore various experimental conditions.